Monoclonal antibodies against loggerhead sea turtle, Caretta caretta, IgY isoforms reveal differential contributions to antibody titers and relatedness among other sea turtles. (October 2018) - Rodgers, Maria L.; Rice, Charles D.
Abstract: Serum from loggerhead sea turtles, Caretta caretta, was collected from the southeast Atlantic Ocean during routine summer monitoring studies in 2017. Serum immunoglobulin IgY was purified and used to develop IgY isoform-specific monoclonal antibodies (mAb). mAb LH12 was developed against the 66 kDa heavy chain of IgY, mAb LH1 was developed against the truncated heavy chain of approximately 37 kDA, and mAb LH9 was developed against the 23 kDa light chains. mAb LH9 reacts with the light chains of all sea turtles, mAb LH12 reacts with the long heavy chain of all sea turtles within the family Cheloniidae, and mAb LH1 reacts with the truncated form of IgY in both olive and Kemp's ridley turtles. Circulating IgY antibodies against three different marine bacterial pathogens were determined in 16 loggerhead samples using these mAbs. mAb LH12 detects higher titers than mAb LH1, and mAb LH9 detects the highest titers. Highlights: Monoclonal antibodies were generated against loggerhead IgY isotypes. mAbs are available for heavy chains, truncated IgY, and light chains. Heavy chain- and light chain-specific mAbs recognize all Cheloniidae turtles. Truncated IgY chain-specific mAb recognizes loggerheads, olive ridleys, and Kemp's ridleys. Contribution of IgY isotypes to antibody titers against marine bacteria were determined.